Seabirds of Easter Island, Salas y Gómez Island and Desventuradas Islands, southeastern Pacific Ocean - Marcelo A Flores (Latin American Journal of Aquatic Research, 2014)
We reviewed available information on seabirds inhabiting Easter Island, Salas y Gómez Island and Desventuradas Islands and their adjacent waters through an analysis of published and grey literature. Results obtained indicate that a total of 37 species are present in the study area and that, among the orders represented, the Procellariiformes and Charadriiformes are the dominant taxa (29 species). Moreover, the family Procellariidae is represented by 13 species and Laridae by 7 species. There has been an increase in new records over the past six years but no systematic studies have been developed. The need for further research that focuses on ecological aspects and anthropogenic impacts is critical in order to develop adequate conservation strategies.